PENGARUH KEPUTUSAN INVESTASI, PENDANAAN, KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Sektor Property dan Real Estate Di Bursa Efek Indonesia Periode 2011-2014) - muharti muharti; risqa anita (Universitas Lancang Kuning, 2017)
Abstract: This study aims to examine the effect of investment decisions, funding and dividend policy on corporate value. The sample in this study are property and real estate companies listed in Indonesia Stock Exchange period 2011 - 2014 as many as 17 companies. To test the hypothesis of this research, data analysis tool used is SEM-PLS by using WarpPLS 6.0 software. The results of this study indicate that investment decisions have a positive impact on firm value. So also with funding decisions that have a positive effect on the value of the company. And finally the dividend policy has a positive effect on the value of the company. Of the three variables, the funding decision is an important variable in influencing the value of the company Because it has a powerful effect size (practical value).Keywords: Investment decision, funding decision, dividend policy, corporate value